2017
DOI: 10.1021/acs.jpca.7b01765
|View full text |Cite
|
Sign up to set email alerts
|

Global and Local Partitioning of the Charge Transferred in the Parr–Pearson Model

Abstract: Through a simple proposal, the charge transfer obtained from the cornerstone theory of Parr and Pearson is partitioned, for each reactant, in two channels: an electrophilic, through which the species accepts electrons, and the other, a nucleophilic, where the species donates electrons. It is shown that this global model allows us to determine unambiguously the charge-transfer mechanism prevailing in a given reaction. The partitioning is extended to include local effects through the Fukui functions of the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…This way, they have been amply used, together with the principles mentioned, to analyze the chemical reactivity of a molecule, and through it, a wide variety of chemical interactions have been described successfully. In particular, the use of Equation , in which all the terms associated with changes in the external potential have been neglected, provides a simplified, but very useful, approach to describe charge transfer processes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This way, they have been amply used, together with the principles mentioned, to analyze the chemical reactivity of a molecule, and through it, a wide variety of chemical interactions have been described successfully. In particular, the use of Equation , in which all the terms associated with changes in the external potential have been neglected, provides a simplified, but very useful, approach to describe charge transfer processes …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the use of Equation (4), in which all the terms associated with changes in the external potential have been neglected, provides a simplified, but very useful, approach to describe charge transfer processes. [2,8,43,[99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115] However, despite the positive aspects of DFT-CR, one must recognize that there are some pending issues, particularly the dependence of the energy with respect to N. In the next section, we will analyze the situation of the behavior of E versus N at a temperature of 0 K, to show the problems that arise, and in the other sections, we will discuss the temperature dependent approach. In the past, there have been important contributions to several aspects concerned with the effects of temperature in the description of DFT-CR.…”
Section: Introductionmentioning
confidence: 99%
“…To assess both the electron flux direction and CT, we calculated, through the FMO approximation, the chemical potential ( μ = ∂E / ∂N ) and chemical hardness ( η = ∂ 2 E / ∂N 2 ) of distorted geometries of reactants at their saddle points. CT values were obtained by relating μ = ∂E / ∂N of the fragments with respect to η = ∂ 2 E / ∂N 2 , whereas donation and back‐donation features were estimated by relating the ionization potential ( I ) and electron affinity ( A ) values of the fragments . Such calculations were performed by using the abovementioned M06‐2X method, but the diffuse functions (6‐311G(d,p)) were removed because the A values became essentially zero upon adding such functions to the basis sets .…”
Section: Resultsmentioning
confidence: 99%
“…Invoking the same reasoning that was used to introduce the local reactivity in the PP model, 34,35 we write eq 8 in atomic resolution:…”
Section: Local Model Within the 2pmmentioning
confidence: 99%
“…In the work where the concepts of electrodonating and electroaccepting powers were introduced by GCV, they also presented the extension of the global 2PM to a local version that lead to the definition of the local electrodonating and electroaccepting powers . In this derivation it is shown that the change in the energy where one distinguishes the donating (−) and the accepting (+) directions of charge transfer is given by that allows one to define a local energy change per unit volume for each direction of charge transfer as Invoking the same reasoning that was used to introduce the local reactivity in the PP model, , we write eq in atomic resolution: where f k ± is the condensed Fukui function (CFF). , With a atoms from fragment or reactant A and b from fragment or reactant B, in the same spirit as it was done in ref , the atomically resolved interaction energy can be expressed as In this last equation nucleophile A participates with a atoms, and the electrophile B with b atoms, resulting in an atomically resolved interaction energy that depends on the number of atoms selected, fact that is indicated by the ab subindex. Minimizing eq with respect to Δ N A – , and conserving the number of electrons in the reaction we obtain that the number of electrons donated by fragment A is given by and the corresponding energy change is …”
Section: Local Model Within the 2pmmentioning
confidence: 99%